2019
DOI: 10.31557/apjcp.2019.20.8.2477
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Lymphoblastic Leukemia: Results of a Case-Control Study

Abstract: Background: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. Different environmental factors might be effective in the occurrence of this malignancy during childhood. The aim of this study was to find environmental risk factors in childhood ALL in Hamadan, Iran. Methods: This case-control study was done in 2015-2018 on 125 children younger than 15 years of age suffering from ALL. Patients were matched with 130 controls with respect to age, gender, and residence location. The identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
1
19
0
3
Order By: Relevance
“…The details of included studies for the subsequent subgroup analysis are shown in Additional file 1: Table S3. Moreover, after excluding studies with the breastfeeding only as dichotomous variable, and no sufficient data of the number of cases and controls in each breastfeeding category, 23 studies were included for leukemia [ 13 , 14 , 18 , 34 36 , 38 43 , 46 , 47 , 54 , 56 , 58 , 61 , 63 , 64 , 70 72 ], 6 studies for lymphoma [ 14 , 33 , 36 , 40 , 43 , 46 ], and 6 studies for brain tumors [ 14 , 40 , 44 , 51 , 64 , 67 ] in dose-response meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of included studies for the subsequent subgroup analysis are shown in Additional file 1: Table S3. Moreover, after excluding studies with the breastfeeding only as dichotomous variable, and no sufficient data of the number of cases and controls in each breastfeeding category, 23 studies were included for leukemia [ 13 , 14 , 18 , 34 36 , 38 43 , 46 , 47 , 54 , 56 , 58 , 61 , 63 , 64 , 70 72 ], 6 studies for lymphoma [ 14 , 33 , 36 , 40 , 43 , 46 ], and 6 studies for brain tumors [ 14 , 40 , 44 , 51 , 64 , 67 ] in dose-response meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 5 Serious Lingappa, 2018, India [ 71 ] 2015 HC-CS 120/120 1–15 Kidwai Institute of Oncology the elder sibling of the cases Leukemia ( N = 120) Never/< 4/4–6/6–9/ 9–12/13–18/ 19–24/> 24;Ever vs. never Interview of mothers Matched: parental education, socioeconomic status, and the region of residence.Adjusted: none. 5 Moderate Rafieemehr, 2019, Iran [ 72 ] 2015–2018 HC-CS 125/130 1–12 Be’sat Hospital of Hamadan University of Medical Sciences Hospital (healthy subjects) ALL ( N = 125) Ever vs. never; 1–3/4–6/7–9/ 10–12/≥ 24 Interview of parents Matched: age, sex, gender, and residence location.Adjusted: none. 6 Serious Bauer, 2020, France [ 73 ] 2015–2018 PC-CS 112/996 0.5–11 ESTELLE, 2010–2011 Population Wilms tumor ( N = 112) Never/ < 3/3–5/≥ 6; Ever vs. never Telephone interview of mothers Matched: age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…En Irán, en 125 menores de hasta 15 años con LLA pareados con 130 niños por la edad, género y localidad de residencia, los autores encontraron que los menores con padres que no tenían un elevado nivel educativo, tuvieron un riesgo (OR) de 2,67, IC 95% (1,45) comparado con los menores con padres que tenían un alto nivel educativo 40 . En China, los investigadores encontraron un riesgo elevado entre los que no tenían o tenían un bajo nivel educativo 20 .…”
Section: Discussionunclassified
“…En esta investigación, también se evaluó el género y la edad de los menores de 14 años, la edad de la madre y el antecedente de evento traumático, ninguno de ellos, se asoció a LLA. Otros investigadores, tampoco han encontrado asociación entre el género de los niños o adolescentes y el riesgo de padecer LLA 38,40 . Se ha identificado que el pico de la incidencia de la LLA está entre los 2 y 5 años 42 .…”
Section: Discussionunclassified
See 1 more Smart Citation